Relative accessibility of district centres in Slovakia by public transport in 2003 and 2017 - Daniel Michniak; Vladimír Székely (European Spatial Research and Policy, 2019)
Transformation of the transport system in Slovakia after 1989 has influenced the pattern of public transport. This article focuses on the analysis of public transport accessibility in district centres in Slovakia. The results show a decrease of connectivity in the network of direct bus and train connections and also a decrease in the number of direct connections between district centres in Slovakia in the period from 2003 to 2017. The main factors that have caused these changes include growing motorisation and individual automobile transport, zero-fare trains for selected categories of inhabitants since 2014, the construction of the motorway network, and the liberalisation of the public transport market.